Pengaruh Pertumbuhan Ekonomi terhadap Tingkat Pengangguran Terbuka di Kota Prabumulih - Rika Rahmadina Putri; Puspa Utami; Nita Talia (Assyarikah: Journal of Islamic Economic Business, 2023)
This study aims to analyze the effect of economic growth on the open unemployment rate in Prabumulih City. The research data used is secondary time series data for the 2010-2021 period obtained from the publication of the Prabumulih City Statistics Agency (BPS). The regression model in this study is a simple linear regression analysis method and is processed with the help of Statistical Package for the Social Sciences (SPSS) 23 software. The analysis technique uses simple linear regression techniques and the results of the equation of this study show that economic growth increases the value of unemployment by 4.534 and the regression coefficient shows that an increase in economic growth increases unemployment by 0.392, this study also shows that the R Square value is 0.246 this figure shows that the economic growth variable affects unemployment by 24.6% and the remaining 75.4% is influenced by other variables outside this study. And from the results of the t test which shows that the t count of the Economic Growth variable is 1.808> t table 0.5760, meaning that the instrument in this study is valid H1 Accepted and a significant level of 0.101> 0.05, this indicates that economic growth has an effect and is not significant on the unemployment rate in Prabumulih City.